Investigation on host specificity of Pantoea stewartii subspecies stewartii strains isolated from jackfruit (Artocarpus heterophyllus) infected with bronzing disease in Malaysia - Mazlan, Safwan; Mohamed Zulperi, Dzarifah; Yusof, Siti Nurdiyana; Abidin, Nuraizat; Ismail Suhaimy, Noor Wahida; Ismail, Siti Izera; Yusof, Mohd Termizi (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
A new disease of jackfruit (Artocarpus heterophyllus) known as fruit bronzing was observed in the Pahang state of Malaysia between 2016 to 2017. Symptoms included yellowish-orange to reddish discoloration of the affected pulps and rags in the fruit. This disease is caused by Pantoea stewartii subspecies stewartii (P. stewartii subsp. stewartii), a Gram-negative bacterium that primarily infected corn. It produced typical bacterial wilt or Stewart's wilt disease symptom in corn, sorghum, sudangrass, oat, triticale, and foxtail millet as well as localized rotting in pineapple. The aim of this study is to assess and evaluate the pathogenicity of P. stewartii subsp. stewartii in different local jackfruit cultivars and its other host plants. Three bacterial strains, which were earlier confirmed as of P. stewartii subsp. stewartii through phenotypic and molecular characterization were subjected to pathogenicity test in three different commercial jackfruit cultivars; J32, J33 and Cj3, and to other host plants genus; cucumber and pineapple. The emergence of bronzing symptom and disease severity were recorded daily up to 14 days of inoculation. After two weeks of incubation, the pathogen was re-isolated from infected fruits in order to complete Koch’s Postulates. Reddish-brown symptom was induced in the inoculated jackfruit, but at different time rate for each variety. As for pineapple, the symptom of localized ring was observed, while in inoculated cucumber produced wilting and changed of color from green to yellow. The outcome of this study is expected to enhance our understanding on pathogenic diversity of P. stewartii subsp. stewartii in various local jackfruit cultivars and other major hosts of the bacterium.